Impact of COVID-19 lockdown and social distancing policies on small businesses in south-eastern Nigeria: whither the stimulus packages?. (1st June 2021) - Iwuoha, Victor Chidubem; Aniche, Ernest Toochi; Ezirim, Gerald Ekenedirichukwu; Alumona, Ikenna Mike; Obiorji, Josephine Nneka
Abstract : This article examines the specific or sub-sectoral effects of COVID-19 lockdown measures on small business units, thus departing from previous studies which only focused on general effects. Based on qualitative and cross-sectional survey methods, the article depicts a cross-sectoral disparity in the patronage level and income stream of customers of small businesses found on the streets of south-eastern Nigeria. The article identifies the gap in the policy interventions meant to cushion the negative impacts of COVID-19 lockdown and social distancing policies on small businesses. Hence, state policy interventions have not had the cushioning impact on small businesses in south-eastern Nigeria. A pro-poor approach towards the review of the policy interventions is highly imperative.